Effectiveness of the mobile Stress Autism Mate Junior application in reducing stress and improving quality of life in adolescents with autism: a pilot study - Alvin van Asselt; Kirsten Hoeberichts; Kirsten Hoeberichts; Sevda Demirel; Sevda Demirel; Anke Scheeren; Anke Scheeren; Yvette Roke (Frontiers in Psychiatry)
ObjectiveStudies indicate that stress levels of autistic adolescents may be particularly high. Therefore, support is needed to help them deal with their stressors. Stress Autism Mate (SAM) Junior, a mobile self-help tool, was designed in co-creation with adolescents with autism to help reduce daily stress levels. The app is based on the SAM app, which was previously shown to be effective in reducing stress in autistic adults. This study aimed to evaluate the effectiveness of the SAM Junior app in reducing perceived stress and maladaptive coping styles, and increasing adaptive coping styles and quality of life in adolescents with autism.MethodsA total of 24 Dutch adolescents with autism participated in this Single Case Experimental Design study. Sixteen of them (9 girls and 7 boys; Mage = 15.0 years, SD = 1.9) completed all research phases. Data were collected at four time points separated by four weeks: Control, pre-test, post-test and follow-up. Linear mixed-effects models were used to analyze the data.ResultsAt post-test, use of the SAM Junior app had no significant effects on participants’ perceived stress (B = 0.31; 95% CI [-1.59, 2.22], p = .73), adaptive coping (B = -1.38; 95% CI [-5.69, 2.94], p = .51), maladaptive coping (B = -0.63; 95% CI [-4.56, 3.30], p = .74) and quality of life (B = -4.13; 95% CI [-12.19, 3.94], p = .29). These non-significant effects persisted at follow-up.DiscussionCurrent preliminary results do not show effectiveness of the SAM Junior app to support adolescents with autism. Using the app as intended, without professional supervision, may have been too complex for this population. Further research is needed to determine the potential effects of the SAM Junior app with more certainty.